Potret Ajaran Tauhid dalam Hadist - M. Jakfar, Tarmizi (Jurnal Pemikiran Islam, 2023)
This article focuses on exploring the depth of the teachings of Tawhid in the Hadiths of Prophet Muhammad SAW and their influence on individual Islamic practices. Through an analytical approach to related hadiths, this study aims to answer three critical questions: (1) What is the position of Tawhid teachings in the Hadiths of Prophet Muhammad SAW?; (2) What criteria for Islam protect an individual's soul and blood from the perspective of the hadiths?; and (3) How do the Hadiths of Prophet Muhammad SAW assess the religious status of a Muslim who commits sins? The findings of this study indicate that Tawhid plays a fundamental role in forming and understanding Islam, where the proclamation of the Shahada is emphasized as the main foundation. This research reveals that faith in Allah SWT is an absolute prerequisite for the acceptance of all other acts of worship. Furthermore, the study observes that while sinful actions do not erase one's Islamic status, the act of shirk (associating partners with Allah) can eliminate that religious status. However, the door of repentance is always open to every Muslim. These findings affirm the importance of the teachings of Tawhid as the core of religious practice.AbstrakArtikel ini berfokus pada eksplorasi kedalaman ajaran tauhid dalam hadis Nabi Muhammad SAW dan pengaruhnya terhadap praktik keislaman individu. Melalui pendekatan analitis terhadap hadis-hadis terkait, studi ini bertujuan menjawab tiga pertanyaan kritis: (1) Apa posisi ajaran tauhid dalam hadis Nabi Muhammad SAW?; (2) Bagaimana kriteria keislaman yang menjaga jiwa dan darah seseorang dalam pandangan hadis?; dan (3) Bagaimana hadis Nabi Muhammad SAW menilai status keberagamaan seorang muslim yang berbuat dosa? Hasil kajian ini menunjukkan bahwa tauhid berperan fundamental dalam pembentukan dan pemahaman keislaman, di mana pengucapan syahadat ditekankan sebagai fondasi utama. Penelitian ini mengungkap bahwa keimanan kepada Allah SWT adalah prasyarat mutlak untuk penerimaan seluruh amal ibadah lainnya. Lebih lanjut, studi ini melihat bahwa meskipun perbuatan dosa tidak menghapus status keislaman seseorang, perbuatan syirik dapat mengeliminasi status keberagamaan tersebut. Namun, pintu taubat selalu terbuka bagi setiap muslim. Temuan ini menegaskan pentingnya ajaran tauhid sebagai pusat dari praktik keagamaan.